The Psychological Impact on Parents of Children who Receive an Inconclusive Diagnosis for Cystic Fibrosis following Newborn Screening: A Systematic Mini-Review - Ioanna Loukou; Maria Moustaki; Konstantinos Douros (MDPI AG, 2024)
Newborn screening (NBS) has been available for the diagnosis of cystic fibrosis (CF) over the last decades. Through the implementation of NBS, a new designation emerged, that of CF related metabolic syndrome (CRMS) or cystic fibrosis screen positive inconclusive diagnosis (CFSPID). As there is uncertainty regarding the clinical progression of these infants to CF, some studies have investigated the psychological impact of CRMS/CFSPID on their parents. This systematic narrative review aimed to describe the findings of the relevant studies. The number of studies is limited and the study samples are relatively small. It seems that there is a negative impact of CRMS/CFSPID on parental mental health. While some studies indicated similar levels of parental anxiety among those with infants diagnosed with CF and those with CRMS/CFSPID, not all studies reached the same conclusion. Parental uncertainty represents another mental dimension of the impact associated with the designation of CRMS/CFSPID. These observations suggest that parents of infants with CRMS/CFSPID should be provided with effective communication, and it may also be beneficial to consider parental mental screening. More robust and long-term studies are required to detect differences in parental emotional status between those with infants diagnosed with CF and those with CRMS/CFSPID.